2020
DOI: 10.1108/jmhtep-07-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Management-led interventions for workplace stress and mental health of academic staff in higher education: a systematic review

Abstract: Purpose This paper aims to focus on management-led intervention strategies aimed at achieving stable mental well-being among academic staff in higher education institutions (HEIs) by reviewing and synthesising existing literature on varying intervention strategies to managing workplace stress and improving mental health. Design/methodology/approach Twenty-two peer-reviewed articles were identified through databases (PsycARTICLES, PsycINFO, Business source complete, Academic search complete) and the applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 21 publications
1
39
0
4
Order By: Relevance
“…Existing research about teacher well-being has identified some significant indicators for job demands and job resources. For job demands, they are workload 24 , which measured mainly through yearly teaching hours and research work (especially for college teachers) 25 , time pressure, which is usually measured with daily working hours 26 , classroom composition, which is reflected in class size and student differences 27 , and performance evaluation 28 ; For job resources, they are work autonomy 29 , 30 , development opportunities 26 , appraisal feedback guide 23 , 24 , 30 , social support from leaders and colleagues 21 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Existing research about teacher well-being has identified some significant indicators for job demands and job resources. For job demands, they are workload 24 , which measured mainly through yearly teaching hours and research work (especially for college teachers) 25 , time pressure, which is usually measured with daily working hours 26 , classroom composition, which is reflected in class size and student differences 27 , and performance evaluation 28 ; For job resources, they are work autonomy 29 , 30 , development opportunities 26 , appraisal feedback guide 23 , 24 , 30 , social support from leaders and colleagues 21 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, the environment in which academic employees function should support the core role of academics (teaching, learning, and research) as well as their goals. Previous studies have found that a supportive environment is beneficial for the mental health of employees (Ohadomere and Ogamba, 2020). Offering academic employees the necessary support will ensure that human resource practices are upheld as the attraction, development, and retention of these employees is increased thereby reducing the cost of turnover (Chaacha and Botha, 2021).…”
Section: Supportmentioning
confidence: 99%
“…The context of this study involves students and faculty staff mental health which are becoming an increasing focus of concern in higher education (HE) discourse (Brewster et al 2021) especially during the Covid 19 pandemic (Shen & Slater, 2021). HE students' mental health has been widely reported as a significant public health challenge internationally (Ohadomere & Ogamba, 2020), with reports suggesting that there is an equal number of students having experienced mental distress prior to their studies and developing symptoms during their studies (Grøtan et al 2019). Studying in HE can be stressful for students particularly if they are new to education which can trigger or exacerbate mental health symptoms (Goodwill et al, 2018).…”
Section: Introduction Mental Health Needs In Higher Educationmentioning
confidence: 99%
“…, 2021) especially during the Covid-19 pandemic (Shen and Slater, 2021). HE students' mental health has been widely reported as a significant public health challenge internationally (Ohadomere and Ogamba, 2020), with reports suggesting that there is an equal number of students having experienced mental distress prior to their studies and developing symptoms during their studies (Grøtan et al. , 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation